MSMES Success Strategy: Unveiling the Secrets of Inspiring Small Business Success - Wahyudin, Ahmad; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Westscience Press, 2023)
Identify and analyze key factors that lead to success in micro, small, and medium-sized enterprises (MSMES). This research aims to provide in-depth insigh into the strategies used by successful MSMES, with the hope of providing practical guidance to other UMKM. The research methods used include surveys, interviews, and analysis of case studies of a number of UMKMs considered successful. The results reveal the secrets of success, including effective marketing strategies, smart financial management, product innovation, superior customer service, and engagement in the local business community. The findings are expected to be a source of inspiration for MSMES owners and prospective entrepreneurs, as well as to make a positive contribution to the development of the UMKM sector as a whole. By understanding and implementing proven successful strategies, MSMES has the potential to increase their competitiveness in the market and long-term success.